The Effect of Patient Wait Time Efficiency on Patient Satisfaction Level - Caesaria Sinta Zuya; Vip Paramarta (PT. Maju Malaqbi Makkarana, 2026)
Patient satisfaction is a key indicator of health service quality and is closely related to loyalty, intention to repeat visit, and institutional reputation 1. Waiting time reflects the efficiency of the process and the responsiveness of services at the stages of registration, administration, and consultation which have a direct impact on the perception of quality and satisfaction 2. Literature review shows a consistent pattern: long wait times decrease satisfaction, while short, predictable wait times increase satisfaction, especially in outpatient services that have higher expectations of timeliness 3. Waiting longer than 60 minutes is associated with a significant decrease in satisfaction scores, making the management of wait time duration and variability crucial. Determining factors include queue design, health worker capacity, administrative complexity, and timeliness of doctors; Meanwhile, digital solutions (e.g. Mobile JKN) speed up the pre-visit and visit process and related to a 5.6 reduction in waiting time. This review summarizes the findings of 2015–2024, maps the determinants and mechanisms of the relationship between wait time and satisfaction, and offers managerial strategies for healthcare facilities in Indonesia and internationally 7